Legal Accountability and Mental Illness: Revisiting the Criminal Responsibility Provisions in the 1946 and 2023 Indonesian Penal Codes - Alwy Shihab Hidayah (Al-Risalah, 2025)
This research aims to analyze the differences in provisions regarding criminal responsibility for individuals with mental disorders as outlined in the Old Indonesian Penal Code (KUHP 1946) and the New Indonesian Penal Code (KUHP 2023), as well as their implications for criminal justice practices. The purpose of the study is to evaluate how each legal framework addresses the accountability of mentally disordered offenders and to assess the legal system’s orientation toward justice and rehabilitation. The methodology employed is normative juridical, incorporating conceptual and statutory approaches. The analysis is based on primary legal materials—namely, the old and new KUHP—as well as secondary sources such as scholarly literature and legal commentaries. The results indicate that the old KUHP provided minimal regulation on offenders with mental illness, often leading to ambiguity in legal processes. In contrast, the new KUHP introduces more comprehensive provisions, explicitly stating that individuals with severe mental disorders are exempt from criminal punishment but may be subjected to medical or rehabilitative measures. The originality of this study lies in its focused comparison between two codifications within the same national legal tradition, highlighting legal evolution over time. The implications emphasize the importance of psychiatric evaluation in ensuring substantive justice and reflect a shift toward a more humane, restorative, and socially protective criminal justice system.